Prevalence, Clinical Presentation, and Outcome of Tuberculosis in Patients with Chronic Kidney Disease at a Tertiary Care Hospital in Nepal - Ravi R. Pradhan; Mahesh Raj Sigdel (International Journal of Nephrology)
Background. Tuberculosis (TB) is a serious public health threat in low- and middle-income countries like Nepal. Chronic kidney disease (CKD) patients are at higher risk of developing new infection as well as reactivation of TB. We aimed to determine the prevalence, clinical presentations, and outcome of TB in patients with CKD in Nepal. Methods. A hospital-based cross-sectional study was performed at Tribhuvan University Teaching Hospital (TUTH), a tertiary level referral centre in Kathmandu, Nepal. We included patients older than 16 years with the diagnosis of CKD stage 3, 4, 5, and 5D (CKD 5 on maintenance dialysis); renal transplant recipients and patients living with HIV/AIDS were excluded. Tuberculosis was diagnosed based on clinical, radiological, and laboratory findings. Prior written informed consent was obtained. Approval was obtained from the Institutional Review Board of the Institute of Medicine. Data entry and statistical analysis were performed using SPSS v21. Results. A total of 401 patients with CKD were included in the study (mean age, 50.92 ± 17.98 years; 64.8% male). The prevalence of TB in CKD patients was found to be 13.7% (55), out of which 49 were newly diagnosed cases. The most common clinical presentations of TB in CKD were anorexia (85.7%), fever (83.7%), weight loss (51%), and cough (49%). Thirty-eight patients (69.1%) had extrapulmonary TB (EPTB), 12 (21.8%) had pulmonary TB, 3 (5.5%) had disseminated TB, and 2 (3.6%) had miliary TB. Only 4.1% of cases were sputum smear positive. Pleural effusion (34.2%) was the most common EPTB. At 2 months of starting antitubercular therapy, 29 patients out of the 49 newly diagnosed cases of TB (59.2%) had responded to therapy. Mortality at 2 months was 28.6% (14 died amongst 49 patients). Four out of 49 patients (8.2%) did not improve, and 2 (4%) patients were lost to follow-up. Conclusion. Prevalence and mortality of TB were higher in patients with CKD. Special attention must be given to these people for timely diagnosis and treatment as the presentation is different and diagnosis can be missed.